EFFECT OF TWO LEGUMES AND RIPE BANANAS AT THE PRODUCTION AND REPRODUCTION OF NEW ZEALAND RABBITS - Sánchez Laiño, Adolfo (2013)
Abstract This study was conducted to evaluate the following objectives: a) Determining the tropical leguminous plant (Pueraria phaseoloides (Roxb) Benth and Gliricidia sepium) and the level of ripe bananas (RB) (50, 75, 100, 100, 125, 150 g animal-1 day-1), as for increasing the reproductive parameters (phase one) and productive (phase two), in New Zealand rabbits. b) Determining the relation benefit / cost of treatments. They were used 28 and 42 rabbits respectively .It was applied a factorial arrangement 2 x 3 + 1, at random completely blocks design (RCBD) with four and three replications. It was used the Tukey test (p≤0.05). The greatest consumption was for kudzu (p<0.01) during phases 1 and 2 (79.97 and 43.26 g dry matter (DM) animal-1 day-1),it increased (p<0.01) weight and litter size at weaning (2165.0 g 5.33). The greatest consumption of RB (p<0.01) was registered on level 3, during phases 1 and 2 (38.39 and 31.39 g DM animal-1 day-1). The consumption of leguminous plant and RB did not affect (p>0.05) the weight of females at birth, the gestation period, weight and litter size at birth. RB levels did not influence (p>0.05) ADG average dairy gain weight gain, feed conversion ratio (FCR), final weight (FW), body weight carcass (BWC) and carcass yield (RC). Treatments based on tropical legumes and RB levels exceeded the control (p<0.01). The greatest profitability in phase 1 and 2 was obtained by combining tropical kudzu 100 and 75 125 g and 100 g BM animal-1 day-1 (30.34 and 29.48%).